THE DIRECT AVOIDANCE OF THE PARTIES IN A SMALL CLAIM COURT IN RESOLVING BUSINESS DISPUTES - Priyono Ongkowijoyo; Ade Candra; Arvhie Laksamana Hanavi; Bestari Soedarman; Muhammad Naufal Rizky (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
In article 4 Paragraph (4) PERMA 4/2019 it was regulated that the troubled entrepreneur in resolving business disputes is required to attend directly, which cannot be represented incidentally, even by a legal representative. However, it turns out that PERMA 4/2019 has not regulated in detail related to the legal consequences of the direct absence of the the troubled entrepreneur. This research is legal research and the approach that this article used is the statute approach and the conceptual approach. The formulation of the problem in this article were: First, the construction of a Small Claim Court and Second in Resolving Business Disputes, Second, the legal consequences of the direct absence of the parties in a Small Claim Court in resolving business disputes. From this research it was found that, First The construction of a Small Claim Court in resolving business disputes that needs to be considered is related to registration, examination of the completeness of a Small Claim Court, determination of judges and appointment of a substitute registrar, preliminary examination, determination of trial day and summons of the parties, trial and reconciliation examination, evidence, and decision and Second the legal consequences of the parties' absence directly in this Small Claim Court in resolving business disputes is the party who is not present in person is considered not to be present at the trial.